AN ANALYZE OF RESEARCH TRENDS ON THE INTERNET OF THINGS (IOT) - Ahmed Atiyah Itwayya; Mohsin N. Al-Maliki; Hasanain A. H. Al-Behadili; Ahmed Jabber Roiss (Journal Park Publishing, 2023)
This study looked at the domestic research trends on the Internet of Things (IoT), which is gaining interest in all fields with the recent development of information and communication technology. They analyzed 101 papers published in academic journals since 2010 with a focus on research topics, research methods, and research fields. Most of the research topics on the Internet of Things were focused on technology and industry, and among them, the proportion of technology was very high. In the technology field, most of the recent technology proposals introducing the technology of the Internet of Things (IoT) have been made. Most of the research methods of the IoT were experimental studies, and a considerable part of the literature review was also occupied. Although the engineering field occupies most of the academic fields that have studied the Internet of Things, there have also been some studies in the social sciences. Considering that the Internet of Things (IoT) has a large ripple effect not only in the industrial field but also socially and culturally, it is necessary to conduct not only technical research but also industrial, service, policy and institutional research through various academic fields and research methods.